The Phase Transition of Half-Skyrmions in the Dense Nuclear Matter - Viet, Nguyen Ai (Communications in Physics, 2014)
In this paper we have discussed all possible boundary values used in the ordinary Skyrme model. Among the solutions to these boundary conditions the non-skyrmion and skyrmion one exist according to certain choices. The free parameter \(R\) in the boundary value conditions is shown to be related to the density of the nuclear matter in its Wigner-Seitz model. All three types of skyrmion can describe the nucleon in a good agreement with the experimental values of the axial coupling constant and isoscalar radii. However, all three types of skyrmion lead to a large value of the nucleon mass and a too small mass splitting between the nucleon and delta particles. The phase transitions of the skyrmions of Type III are also observed in the numerical computations as the density of the nuclear matter varies.